PENETAPAN ANGKA KAPANG KHAMIR (AKK) PADA REMPAH-REMPAH YANG DIJUAL DI PASAR SRI GUNTING MEDAN - Yosy Cinthya Eriwaty Silalahi; Kesaktian Manurung; Putri Niat Salma Halawa (Jurnal Farmanesia, 2020)
Spices containing fungal contamination exceed the stipulated limit of 1x104 colonies/g which will affect the stability of the preparation and aflatoxins that are harmful to health such as liver cancer. This study aims to determine the value of the yeast mold number (AKK) in spices at the Sri Gunting market, Medan. The population in this study were spices in the form of wet powder, namely turmeric (Curcuma longa Linn.), ginger (Zingiber officinale Rosc.), and temulawak (Curcuma xanthorhiza Roxb.), and 250 grams of each ingredient was taken from four spice traders. with location criteria such as on the edge of a highway, near a ditch/gully, inside a kiosk, and near a meat seller as a sample. Subjects of research and observations are presented in the form of tables and figures which are then analyzed descriptively. The results of the study found that the AKK of spices sold at the Sri Gunting market in Medan was equal to trader A (turmeric 16.1x10^4, Ginger 7.9x10^4, Temulawak 11.1x10^4cfu/g), trader B (turmeric > 150, Ginger 11.5x10^4Temulawak 18x10^4cfu/g), merchant C (turmeric 12.2x10^4, Ginger 6.1x10^4, Temulawak 4.5x10^4cfu/g), and merchant D (turmeric >150, Ginger 10.9x10^4, Temulawak >150cfu/g) which means that the AKK contained from spices sold at the Sri Gunting market in Medan does not meet the requirements according to the Food and Drug Supervisory Agency (BPOM).